Avaliação audiológica, metabólica e de qualidade de vida no indivíduo jovem com zumbido usuário de estéreo pessoal - Sumera, Moniane Aparecida [UNESP] (2015)
Hearing health of young adults has been a constant source of concern to health professionals working in this area. This concern is justified considering the habits of these young people, who in their leisure time, attending noisy environments and use personal stereos, habits that have been considered as a public health problem since endanger the hearing health. The literature reports that one of the consequences in young users of personal stereos is complaint about tinnitus. Considering the above, aim of this study was to characterize and compare the audiological profile of individual users or not personal stereos, with and without tinnitus. This is a descriptive and comparative cross-sectional study, conducted in a clinical school at a public university. Comprised the study sample 60 individuals of both genders, aged between 18 and 30 who were divided into four groups: group 1 sample (GA1) composed of 18 individuals users of personal stereos and tinnitus; sample group 2 (GA2) including 22 subjects users of personal stereos and without tinnitus; control group 1 (GC1): composed of 12 individuals who did not use personal stereos and with tinnitus and; control group 2 (GC2): composed of eight individuals who did not use personal stereos and without tinnitus. The evaluation consisted of the following procedures: interview, questionnaire on the description of hearing habits and behavior in relation to exposure to noisy events, Youth Attitude to Noise Scale (YANS), visual inspection of the external auditory canal, pure tone audiometry, tympanometry and, otoacoustic emissions distortion product. It was used the Tinnitus Handicap Inventory (THI), and it was requested laboratory tests for individuals with tinnitus. The results of this study showed no difference in the results of pure tone audiometry and otoacoustic emissions by distortion product between these two groups. By correlating the results of both procedures, it was observed that most of ...